The Knowledge, Practice and Attitudes of Nurses Regarding Physical Restraint: Survey Results from Psychiatric Inpatient Settings - Lee Tsz-Kai; Välimäki Maritta; Lantta Tella (MDPI, 2022)
There is a considerable amount of literature describing how nurses' knowledge contributes to their attitudes and practices related to patient physical restraint. However, whether or not there have been any improvements in nurses' knowledge levels, attitudes or practices regarding physical restraint during the past few years is unknown. A survey was conducted on nurses (n = 133) in one psychiatric hospital in Hong Kong (n = 98, response rate = 74%). The data were analyzed using independent t-tests, ANOVA, a Mann-Whitney U test, a Kruskal-Wallis test and Spearman's rho. In general, nurses had good restraint-related knowledge with satisfactory attitudes and practices, although their knowledge levels, attitudes, and practices regarding restraint varied. Having a higher age, seniority, and education level contributed to a higher restraint-related knowledge level. Male nurses demonstrated more desirable practices (i.e., care of restrained patients), while nurses with a higher education level were more likely to avoid restraint. Nurses' restraint-related knowledge positively correlated with restraint practices. Although nurses' knowledge levels, attitudes, and practices regarding restraint were found to be satisfactory, more training efforts should focus on young nurses working in psychiatric settings with less work experience and lower education levels. As some nurses seem to favor the use of restraint with limited reflection, more studies are needed to verify nurses' emotions and how their emotions influence the use of restrictive practices.